Central versus ambulatory blood pressure for predicting mortality and cardiovascular events in hemodialysis patients: a multicenter cohort study. Issue 1 (January 2022) - Liu, Wenjin; Ye, Yinyin; Wang, Lulu; Gao, Chaoqing; Bai, Youwei; Chu, Hong; Fan, Wei; Sun, Zhuxing; Wang, Liang; Li, Xiurong; Yang, Junwei
Abstract : Objective: Studies in the general population suggest that central blood pressure (BP) may be superior to peripheral BP in risk assessment. Although ambulatory brachial BP is recognized as the most reliable BP measurement in the dialysis population, there is no comparison of office central BP with ambulatory BP regarding risk stratification in these patients. Methods: In a multicenter prospective study of dialysis patients, central BP was measured noninvasively on a midweek nondialysis day, with interdialytic ambulatory BP and predialysis BP also collected. The primary outcomes were a composite of major adverse cardiovascular events (MACE) and all-cause mortality. Agreement between central and ambulatory BP was assessed using Cohen's Kappa index and Bland–Altman plot. Linear and nonlinear Cox regression models were used to determine the association of BP parameters with outcomes. Results: A total of 368 patients were recruited and 366 underwent central BP measurement. Central BP had a moderate agreement with ambulatory BP in defining hypertension ( κ = 0.42) with wide limits of agreement in Bland–Altman analysis. After a median follow-up of 51.5 months, central pulse pressure, ambulatory SBP and ambulatory pulse pressure were associated with all-cause mortality, whereas all BP parameters, except for predialysis DBP, were significant predictors of MACE. However, whenever evaluated in a stepwise variable selection Cox model, only ambulatory pulse pressure, but not any central BP, was determined as the best candidate for prediction of both all-cause mortality and MACE. Nonlinear Cox models revealed no significant nonlinear trend of the association between central BP and outcomes. Conclusion: Central BP is predictive of all-cause mortality and cardiovascular events in dialysis patients but its prognostic value does not outperform ambulatory peripheral BP. Our data support the superiority of ambulatory BP in the dialysis population. Abstract : Supplemental Digital Content is available in the text